Co2+ and Ho3+ doped CuS nanocrystals with improved photocatalytic activity under visible light irradiation. Issue 48 (29th April 2016) - Hosseinpour, Zahra; Hosseinpour, Sara; Maaza, Malik; Scarpellini, Alice
Abstract : Co 2+ and Ho 3+ doped CuS nanostructures have been synthesized by a hydrothermal method. The nature of dopants influence the morphology, photocatalytic performance and the band gap values. Abstract : In this work, Co 2+ and Ho 3+ doped CuS nanostructured assemblies have been synthesized by means of a surfactant free hydrothermal method and investigated as photocatalysts in the degradation of methylene blue (MB) dye under visible light irradiation in the presence of H2 O2 . Firstly, it is found that the nature of dopants (M = Co 2+, Ho 3+ ) plays an important role in controlling the morphology of CuS structures as observed in FESEM and TEM analysis. Secondly, the band gap values of the M doped CuS structures showed a red shift. As a result, the M doped CuS structures exhibited enhanced photocatalytic activities compared to the pristine CuS structures. Among the different photocatalysts tested, 2.5 mol% cobalt doped CuS (CC samples) showed the best activity (∼52% more than CuS) in the photocatalytic degradation of dyes (almost complete degradation (∼99%) of MB dye in 20 min). In addition, these CC samples showed good catalyst stability for the degradation of dyes. The overall differences in the catalytic activity of the samples tested are discussed in terms of their band gap, surface area, porosity, defect surface, and morphology.